2016
DOI: 10.1515/ohs-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton distribution and variation along a freshwater-marine transition zone (Kızılırmak River) in the Black Sea

Abstract: Both phytoplankton of the Kizilirmak River/Black Sea transition zone and their interactions with nutrients were investigated between July 2007 and December 2008. A total of 447 taxa belonging to the divisions: Cyanobacteria (24), Bacillariophyta (209), Bigyra (1), Cercozoa (1), Charophyta (11), Chlorophyta (32), Cryptophyta (11), Miozoa (119), Euglenozoa (14), Haptophyta (13), Ochrophyta (10) and Protozoa Incertae Sedis (2) were identified at 5 different sites in the study area. Seventy four taxa were recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Liman and Sarıkum Lakes, located in Black Sea region, have been influenced mainly by rivers (e.g., Kızılırmak River), and floodwater, only a few marine taxa were observed in these lakes (Sıvacı et al, 2008;Soylu et al, 2011). Nevertheless, low salinity of the Black Sea is suitable for marine and marine-brackish species to establish a community (Baytut & Gönülol, 2016;Kaleli, Kulikovskiy & Solak, 2017). Diatom flora of the two Black Sea lagoons revealed that both lakes were influenced mostly by the freshwater inputs.…”
Section: Resultsmentioning
confidence: 99%
“…Liman and Sarıkum Lakes, located in Black Sea region, have been influenced mainly by rivers (e.g., Kızılırmak River), and floodwater, only a few marine taxa were observed in these lakes (Sıvacı et al, 2008;Soylu et al, 2011). Nevertheless, low salinity of the Black Sea is suitable for marine and marine-brackish species to establish a community (Baytut & Gönülol, 2016;Kaleli, Kulikovskiy & Solak, 2017). Diatom flora of the two Black Sea lagoons revealed that both lakes were influenced mostly by the freshwater inputs.…”
Section: Resultsmentioning
confidence: 99%
“…In the some studies, it is stated that C. cymbiformis var. nonpunctata (Figure 3, m) was previously found by Şahin (1998), Sıvacı and Pabuçcu (2007), Baytut and Gönülol (2016). However, none of the previous studies are on sediment cores and in none of them has been found in fossil records.…”
Section: Resultsmentioning
confidence: 64%
“…In many coastal marine environments mixotrophic cryptophytes (Plagioselmis, Teleaulax, Rhodomonas and Cryptomonas) are part of key components of phytoplankton communities (Cloern & Dufford, 2005;Han & Furuya, 2000). In the Black Sea, only few studies have reported the distribution of cryptophytes in the coastal regions under the influence of Danube (Eker-Develi et al, 2012) and the Kızılırmak River (Baytut & Gonulol, 2016). However, the role of nutritionally rich cryptophytes with the highest organic content per cell volume among microalgae (Moal, Martin-Jezequel, Harris, Samain & Poulet, 1987) is apparently underestimated by cell volume to carbon conversion factors usually used for microalgae groups (Menden-Deuer & Lessard, 2000;Montagnes, Berges, Harrison & Taylor, 1994;Verity et al, 1992).…”
Section: Discussionmentioning
confidence: 99%